2011
DOI: 10.1007/s00122-011-1677-6
|View full text |Cite
|
Sign up to set email alerts
|

Pea powdery mildew er1 resistance is associated to loss-of-function mutations at a MLO homologous locus

Abstract: The powdery mildew disease affects several crop species and is also one of the major threats for pea (Pisum sativum L.) cultivation all over the world. The recessive gene er1, first described over 60 years ago, is well known in pea breeding, as it still maintains its efficiency as a powdery mildew resistance source. Genetic and phytopathological features of er1 resistance are similar to those of barley, Arabidopsis, and tomato mlo powdery mildew resistance, which is caused by the loss of function of specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(157 citation statements)
references
References 25 publications
2
146
0
Order By: Relevance
“…Given that the putative functions of these MLOs in clade V were derived from Arabidopsis, tomato, and pea, we infer that this clade is significant for cucumber because these genes are required for PM susceptibility (Consonni et al, 2006;Bai et al, 2008;Pavan et al, 2011). This clade may thus be a dicot-specific group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given that the putative functions of these MLOs in clade V were derived from Arabidopsis, tomato, and pea, we infer that this clade is significant for cucumber because these genes are required for PM susceptibility (Consonni et al, 2006;Bai et al, 2008;Pavan et al, 2011). This clade may thus be a dicot-specific group.…”
Section: Discussionmentioning
confidence: 97%
“…The distribution of MLO family members in the cucumber genome is depicted in Figure 4. Two CsMLO genes, Csa009424 and Csa017252, were positioned on chromosomes (Pavan et al, 2011), tomato (SlMLO) (Bai et al, 2008), and Arabidopsis (AtMLO02, AtMLO06, and AtMLO12) (Consonni et al, 2006). The positions of the seven TM domains (TM1 to TM7) inferred from the experimentally determined topology of HvMLO (Devoto et al, 1999) and the approximate position of the CaMBD (Kim et al, 2002b) are indicated by lines under the sequences.…”
Section: Locations Of the Mlo Genes On The C Sativus Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally discovered in Hordeum vulgare (barley), mlo immunity has also been found to exist in several plant species later, particularly Arabidopsis . This consequently led to the breeding protocol founded upon the methodical inactivation of MLO susceptibility genes across planted varieties infected by the PM fungi [ 6,9,14 ]. Proof of formalization of this approach has been recently conducted by the experiment, showing the introduction of PM resistance in Triticum aestivum (bread wheat) following targeted mutagenesis of 3 MLO homoeoalleles by the CRISPR-Cas9 and TALEN system [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PM resistance of pea er1 initialing from the loss of function of PsMLO1 was first reported since 1948 and is the sole resistance source internationally used for breeding objectives [ 11,19 ]. Interestingly, when displayed in the evolutionary trees of MLO protein family, all MLO isoforms from dicots experimentally shown to be necessary for PM immunity group in the clade V in the scientific documents [ [8][9][10][20][21][22] ]. Furthermore, clade IV harbors all featured monocot PM perceptivity proteins [ 23 ].…”
Section: Introductionmentioning
confidence: 99%